"Are we to go literally to the hot dogs?" Parking Lots, Drive-ins, and the Critique of Progress in Toronto's Suburbs, 1965–1975 - Penfold, Steve (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2004)
This paper examines reactions to drive-in restaurants in the suburbs of Toronto, Ontario, in the late 1960s and early 1970s. It begins by laying out the main themes of a suburban critique of drive-ins, which were seen as symbols of larger problems of automobile landscapes, urban sprawl, runaway progress, and honky-tonk modernity. Next, the paper focuses more closely on an extended anti-drive-in campaign in Bronte, Ontario, one of many villages swept into the growing suburban sprawl around Toronto after World War II. There, a vocal group of activists rebelled against the nature of development in the area, mounting vigorous resistance to high-rise apartments, increased traffic, gas stations, and fast food restaurants. Drawing on the "pro-people," participatory democracy rhetoric of urban reform movements, Bronte activists pressed their case on municipal institutions and scored some important political victories. In the end, however, the drive-ins remained, since activist ratepayers could not overcome the limitations of zoning as a tool of redevelopment or the decline of citizen activism over the course of the 1970s. More importantly, they had to confront the continued popularity of the car itself, a commodity upon which their own suburban lifestyle depended.